2017
DOI: 10.1002/adhm.201700447
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up Nanoencapsulation from Single Cells to Tunable and Scalable Cellular Spheroids for Hair Follicle Regeneration

Abstract: Cell surface engineering technology advances cell therapeutics and tissue engineering by accurate micro/nanoscale control in cell-biomaterial ensembles and cell spheroids formation. By tailoring cell surface, microgels can encapsulate cells for versatile uses. However, microgels are coated in a thick layer to house multiple cells together but not a single cell based. Besides, excessive deposition on cell surface is detrimental to cellular functions. Herein, layer-by-layer (LbL) self-assembly to encapsulate sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 53 publications
(52 reference statements)
1
32
0
Order By: Relevance
“…In vivo experiment by nude mice showed that this nanogel–cell complex exhibited no toxicity, and hair shafts were induced in 4 weeks. [ 112 ] Problems of immune response has also been solved using material integration strategy. Pluripotent stem cells (PSCs) are capable for treating myocardial infarction (MI); however, with low concentration and short retention time, the effects cannot be guaranteed.…”
Section: Biomedical Applications Of Materials Integrated Organismsmentioning
confidence: 99%
“…In vivo experiment by nude mice showed that this nanogel–cell complex exhibited no toxicity, and hair shafts were induced in 4 weeks. [ 112 ] Problems of immune response has also been solved using material integration strategy. Pluripotent stem cells (PSCs) are capable for treating myocardial infarction (MI); however, with low concentration and short retention time, the effects cannot be guaranteed.…”
Section: Biomedical Applications Of Materials Integrated Organismsmentioning
confidence: 99%
“…C) Schematic illustration of the construction of dermal papilla spheroids by aggregation of LbL encapsulated dermal papilla cells for hair follicle regeneration. Adapted with permission . Copyright 2017, Wiley‐VCH.…”
Section: Biomedical Applications Of Lbl Self‐assembly For Cell Encapsmentioning
confidence: 99%
“…Apart from constructing biomimetic tissues by LbL encapsulating cell with nanometer‐sized fibronectin–gelatin films, biomimetic tissues can also be prepared by physical cross‐linking on LbL encapsulated cells to form the cell spheroids . For example, our group previously reported the fabrication of dermal papilla spheroids for hair follicle regeneration, as shown in Figure C. Individual dermal papilla cells were encapsulated with gelatin and alginate by LbL assembly to form ultrathin nanocoated matrices.…”
Section: Biomedical Applications Of Lbl Self‐assembly For Cell Encapsmentioning
confidence: 99%
“…For instance, alginate is a natural polysaccharide derived from algae, and gelatin is a protein derivative. Owing to their biocompatibility and biodegradability, these substances have been widely used in ECM tissue engineering 28 - 32 . In the current study, gelatin and alginate were used to coat HFSCs in the engineering of nanoscale biomimetic ECM for individual cells.…”
Section: Introductionmentioning
confidence: 99%